Pharmaco-economics Study: A cost variation analysis of various statin preparations available in Nepali market - Karki, Sirisa; Paudel, Gita; Bhurtyal, Karma Murti (Nepal Mediciti Medical Journal, 2020)
Background: Hyperlipidemia is one of the greatest risk factors contributing to prevalence and severity of cardiovascular diseases. Treatment of hyperlipidemia with statins have proven efficacy in reduction of cardiovascular events. In the present study, we aim to find out the variation in cost of commercially available statin products in Nepal. Methods: The price of different statin products with same formulation and strength was obtained from various medicine importers and distributors inside Kathmandu valley, Pokhara and Chitwan. Percentage of cost variation and cost ratio was calculated. Results: High percentage of cost variation was observed among Indian product with Atorvastatin 10 mg (898.8% Cost ratio: 9.98) followed by Atorvastatin 20mg (894.52% Cost ratio: 9.94). Least percentage of cost variation was observed with Nepal manufactured Atorvastatin 5mg (49.62 Cost ratio: 1.49).Conclusion: There is a wide percentage of cost variation with available statins in the Nepali market. Regulation of drug price by concerned agencies and by government should be a national priority. Rational drug prescription with low cost is important for treatment adherence and disease outcome